2002
DOI: 10.1007/s10350-004-6260-7
|View full text |Cite
|
Sign up to set email alerts
|

Previous Sphincter Repair Does Not Affect the Outcome of Repeat Repair

Abstract: Previous sphincter repair does not affect clinical outcome. Repeat anterior overlapping sphincter repair yields a significant improvement in the continence score and should be considered as the treatment of choice in patients with fecal incontinence who have had previous sphincter repair and residual anterior sphincter damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 39 publications
2
16
1
4
Order By: Relevance
“…[23][24][25][26][27][28] In our unpublished series of 16 patients, the success rate was 81 percent after a median of 12-month follow-up. Although it has been reported that previous sphincter repair does not affect the outcome of repeat repair, 29 in the light of our experience with primary and secondary repairs, we are convinced that if the primary repair is performed with meticulous technique, only a small portion of these patients will need secondary repair. Because of the sensitive nature of the problem, not all patients with fecal incontinence after childbirth seek medical attention.…”
Section: Discussionmentioning
confidence: 60%
“…[23][24][25][26][27][28] In our unpublished series of 16 patients, the success rate was 81 percent after a median of 12-month follow-up. Although it has been reported that previous sphincter repair does not affect the outcome of repeat repair, 29 in the light of our experience with primary and secondary repairs, we are convinced that if the primary repair is performed with meticulous technique, only a small portion of these patients will need secondary repair. Because of the sensitive nature of the problem, not all patients with fecal incontinence after childbirth seek medical attention.…”
Section: Discussionmentioning
confidence: 60%
“…15,23 The results of this study demonstrate a continuing acceptable rate of patient satisfaction (60 percent) with the outcome of repeat anterior sphincter repair at a median follow-up of 60 months. This rate is similar to the best results that have been reported for alternative procedures.…”
Section: Discussionmentioning
confidence: 82%
“…69 Up to 60 percent of patients complain of incontinence after a sphincteroplasty. 70 Giordano et al 70 performed a repeat sphincteroplasty in 36 patients (Table 2). After a median follow-up of 13 months, half the patients had a good outcome.…”
Section: Anal Plugmentioning
confidence: 98%
“…However, the outcome after three or more repeat sphincter repairs is uncertain. 70 Recent studies have shown that a concomitant diverting stoma was not necessary. 73,74 In a randomized trial on sphincteroplasty with or without a diverting stoma, 74 the authors concluded that fecal diversion gave no benefit in terms of wound healing or functional outcome.…”
Section: Anal Plugmentioning
confidence: 99%